Studying Müllerian duct anomalies - from cataloguing phenotypes to discovering causation - Laura Santana González; Mara Artibani; Ahmed Ashour Ahmed (The Company of Biologists, 2021)
Müllerian duct anomalies (MDAs) are developmental disorders of the Müllerian duct, the embryonic anlage of most of the female reproductive tract. The prevalence of MDAs is 6.7% in the general female population and 16.7% in women who exhibit recurrent miscarriages. Individuals affected by these anomalies suffer from high rates of infertility, first-trimester pregnancy losses, premature labour, placental retention, foetal growth retardation and foetal malpresentations. The aetiology of MDAs is complex and heterogeneous, displaying a range of clinical pictures that generally lack a direct genotype-phenotype correlation. De novo and familial cases sharing the same genomic lesions have been reported. The familial cases follow an autosomal-dominant inheritance, with reduced penetrance and variable expressivity. Furthermore, few genetic factors and molecular pathways underpinning Müllerian development and dysregulations causing MDAs have been identified. The current knowledge in this field predominantly derives from loss-of-function experiments in mouse and chicken models, as well as from human genetic association studies using traditional approaches, such as microarrays and Sanger sequencing, limiting the discovery of causal factors to few genetic entities from the coding genome. In this Review, we summarise the current state of the field, discuss limitations in the number of studies and patient samples that have stalled progress, and review how the development of new technologies provides a unique opportunity to overcome these limitations. Furthermore, we discuss how these new technologies can improve functional validation of potential causative alterations in MDAs.